Formation of G-quadruplex and its utilizing for an automated spectrometric detection of cisplatin - Ruttkay-Nedecký, Branislav; Skaličková, Sylvie; Kremplová, Monika; Nejdl, Lukáš; Kudr, Jiří; Hynek, David; Novotná, Marie; Labuda, Jan; Adam, Vojtěch; Kizek, René (ESG, 2015)
Here, we studied the formation of G-quadruplex using spectrophotometric methods (peroxidase activity of G-quadruplex) and verifications of obtained results by voltammetry (cytosine-adenine (CA) or guanine (G) peaks height). The results showed that the peroxidase activity of G-quadruplex increases with the increasing concentrations of K+ ions (1-20 mM) and Na+ ions (1-5 mM) with the highest values observed in the presence of K+ ions. The reverse trend was obtained with NH4+ ions, where the highest peroxidase activity was observed at the lowest concentration of NH4+ ions. The G-quadruplex formation was also proven electrochemically. The addition of 5 mM of K+ ions to the oligonucleotide solution with hemin caused a decrease of both determined peaks. The peroxidase activity of G-quadruplex increased with the increasing concentration of Ag+ ions within the range from 40 nM to 5 mu M. Further, the addition of different concentration of cisplatin (0.5-2 mu M) to the G-quadruplex was monitored. With the addition of cisplatin there was a decrease in peroxidase activity and simultaneously decrease in the CA peak height with the greatest effect in twentieth minute after the addition of cisplatin. The G-quadruplex coupling with gold magnetic nanoparticles was performed and the possibility of automation of spectrophotometric assay was proven

Here, we studied the formation of G-quadruplex using spectrophotometric methods (peroxidase activity of G-quadruplex) and verifications of obtained results by voltammetry (cytosine-adenine (CA) or guanine (G) peaks height). The results showed that the peroxidase activity of G-quadruplex increases with the increasing concentrations of K+ ions (1-20 mM) and Na+ ions (1-5 mM) with the highest values observed in the presence of K+ ions. The reverse trend was obtained with NH4+ ions, where the highest peroxidase activity was observed at the lowest concentration of NH4+ ions. The G-quadruplex formation was also proven electrochemically. The addition of 5 mM of K+ ions to the oligonucleotide solution with hemin caused a decrease of both determined peaks. The peroxidase activity of G-quadruplex increased with the increasing concentration of Ag+ ions within the range from 40 nM to 5 mu M. Further, the addition of different concentration of cisplatin (0.5-2 mu M) to the G-quadruplex was monitored. With the addition of cisplatin there was a decrease in peroxidase activity and simultaneously decrease in the CA peak height with the greatest effect in twentieth minute after the addition of cisplatin. The G-quadruplex coupling with gold magnetic nanoparticles was performed and the possibility of automation of spectrophotometric assay was proven
Formation of G-quadruplex and its utilizing for an automated spectrometric detection of cisplatin
Keywords: G-quadruplex; Silver Ions; Cisplatin; Spectrophotometric Methods; Square Wave Voltammetry; Cyclic Voltammetry; G-quadruplex; Silver Ions; Cisplatin; Spectrophotometric Methods; Square Wave Voltammetry; Cyclic Voltammetry